A Comparison Between Body Weight-Supported Treadmill Training and Conventional Over-Ground Training in Dogs With Incomplete Spinal Cord Injury - Martins, Ângela; Gouveia, Débora; Cardoso, Ana; Viegas, Inês; Gamboa, Óscar; Ferreira, António (Frontiers in Veterinary Science, 2021)
In human medicine there was no evidence registered of a significant difference in recovery between body weight-supported treadmill training (BWSTT) and conventional over-ground (COGI). There isn´t any similar study in veterinary medicine. Thus, this study aimed to compare the locomotor recovery obtained in incomplete SCI (T11–L3 Hansen type I) post-surgical dogs following BWSTT or COGI protocols, describing their evolution during 7 weeks in regard to OFS classifications. At admission, dogs were blindly randomized in two groups but all were subjected to the same protocol (underwater treadmill training) for the first two weeks. After, they were divided in the BWSTT group (n=10) and the COGI group (n=10) for the next two weeks, where they performed different training. In both groups locomotor training was accompanied by functional electrical stimulation (FES) protocols. Results reported statistically significant differences between all OFS evaluations time-points (p<0.001) and between the two groups (p<0.001). In particular with focus on T1 to T3 a two-way repeated measures ANOVA was performed and similar results were obtained (p=0.007). Functional recovery was achieved in 90% (17/19) of all dogs and 100% recovered bladder function. The BWSTT group showed 100% (10/10) recovery within a mean time of 4.6 weeks, while the COGI group had 78% (7/9) within 6.1 weeks. Therefore, BWSTT leads to a faster recovery with a better outcome in general.